2017
DOI: 10.1097/bpb.0000000000000426
|View full text |Cite
|
Sign up to set email alerts
|

Normal radiographic parameters in paediatric pelvic radiographs from a Chinese population

Abstract: Diagnostic Study Level III - Study of nonconsecutive patients (without consistently applying the reference 'gold' standard).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Fortunately, the acetabular index measured by deep learning system in the normal group and the abnormal group, using the Bland–Altman principle, both showed good credibility. In addition, the acetabular index declined more rapidly in the first 3 months of life and then changed more rapidly between the ages of 1 and 5 years ( 20 ). Therefore, we divided the cases into four different age groups, and the results showed that the consistency of measured acetabular index in infants under six months of age was worse than that in the other three groups.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, the acetabular index measured by deep learning system in the normal group and the abnormal group, using the Bland–Altman principle, both showed good credibility. In addition, the acetabular index declined more rapidly in the first 3 months of life and then changed more rapidly between the ages of 1 and 5 years ( 20 ). Therefore, we divided the cases into four different age groups, and the results showed that the consistency of measured acetabular index in infants under six months of age was worse than that in the other three groups.…”
Section: Discussionmentioning
confidence: 99%
“…The ultrasound and radiographic recovery criteria were as follow: (a) type-I hip according to Graf classification [7] and (b) well-reduced hip on plain radiographs with acetabular index (AI) no more than one SD above the mean value for normal age matched children, as reported by Shi et al . [15,16]. Patients were then divided into two groups whether they met recovery criteria (ultrasound or radiographic) or not: (a) group A: patients meeting recovery criteria and (b) group B: patients not meeting recovery criteria.…”
Section: Methodsmentioning
confidence: 99%
“…PAD was diagnosed if: (a) AI in patients younger than 4 years was greater than 1 SD than the mean value for normal age matched children [15,16,20], or there was evidence of subluxation; (b) patients older than 4 years had grade III or IV hips according to Severin classification [21]; and (c) no evidence of break in Shenton’s line.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiographic dysplasia was defined as AI values > 2 SD from age, sex, and laterality-specific normal values previously defined by Tönnis 18 and Kuong et al 19 If any side of the hip had dysplasia, it was judged as a patient with dysplasia.…”
Section: Radiographic Measurementsmentioning
confidence: 99%